Abundant exact soliton solutions to the Fokas system - Wang, Kang-Jia (Optik (Stuttgart), 2022)
In the current work, we consider the Fokas system that describes the nonlinear pulse propagation in monomode optical fibers. By employing the Exp-function method, we succeed in constructing six families(eleven sets) of the exact soliton solutions. And the behaviors of the real, imaginary and absolute parts of the solutions are described through the 3-D contours. It reveals that the Exp-function method is an effective method to construct abundant exact solutions for the partial differential equations arising in optics.